If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x2-2x+3=x2+x-4
We move all terms to the left:
x2-2x+3-(x2+x-4)=0
We add all the numbers together, and all the variables
-(+x^2+x-4)+x2-2x+3=0
We add all the numbers together, and all the variables
x^2-(+x^2+x-4)-2x+3=0
We get rid of parentheses
x^2-x^2-x-2x+4+3=0
We add all the numbers together, and all the variables
-3x+7=0
We move all terms containing x to the left, all other terms to the right
-3x=-7
x=-7/-3
x=2+1/3
| 2500+150x=12 | | 12-8x=56 | | 12-8=56x | | 3f+13-4f=-5f+9 | | Y+5=2g-13 | | 7d-2d+9=34 | | 8.01=p+4.49 | | 2n=5n=6 | | 4x+18=1.5x+4 | | 8=4(g-17 | | x^2+9x-486=0 | | 9n+10=6n-20 | | 7m-3m+11=31 | | 8-4=2y-5 | | x+0.8x=126 | | x=8.9+6.2 | | C=y+15 | | 13x+7=3x-3 | | 8x+5=2x-18 | | 18y-12=8-8y | | 10a-2=2a+22 | | y=25=100 | | 3a+8=-1.24 | | 5n=3n+60 | | 0=-200/500x+2900 | | (x-1)(x3-14x2+49x-36)=-36 | | x3-14x2+49x-36=-36 | | 5(2p-3)-3(3p-7)=7 | | 4/n=5/21 | | 81^3x-4=27 | | x-20+3x+6=90 | | x-12.4x=25 |